PENGALAMAN PENGGUNAAN PRE-EXPOSURE PROPHYLAXIS (PREP) BERDASARKAN TEORI TRANSTEORITIKAL MODEL (TTM) PADA LSL DI KOTA TANGERANG - Amin, Ahmad Farid; Dewi Purnamawati; Siti Nurfadhilah; Toha Muhaimin; Armein Sjuhary Rowi (Public Health Study Program, Faculty of Health Science, State Islamic University (UIN) Syarif Hidayatullah Jakarta, Indonesia., 2025)
Pre-Exposure Prophylaxis (PrEP) is an effective method for preventing Human Immunodeficiency Virus (HIV) among Men Sex Men (MSM), but its uptake in Tangerang City remains low. This study explores the experiences of MSM using PrEP based on the Transtheoretical Model (TTM) in Tangerang City. Conducted from January to June 2024, this descriptive qualitative research involved three key informants and two supporting informants from healthcare and community services, selected purposively. Content analysis was employed to examine the TTM stages: precontemplation, contemplation, preparation, action, and maintenance. In the precontemplation stage, MSM continue risky sexual behaviors despite recognizing HIV risks. During contemplation, they demonstrate good knowledge about HIV and PrEP and express a strong intention to start PrEP. The preparation stage underscores the importance of community and healthcare support in initiating PrEP. In the action stage, many MSM face side effects like nausea and dizziness. In the maintenance stage, despite awareness and support, side effects, boredom, and the belief of reduced risk lead MSM to discontinue PrEP. All informants experienced the five TTM stages, but two of three discontinued PrEP at the maintenance stage. Intensive initial support is crucial to manage side effects and ensure adherence to PrEP. Keywords: HIV, MSM, PrEP